The Role of Leadership Style and Motivation in Improving Employee Performance - Fitriyah, Nabilatul; Sukasmono, Tri; Qomariyah, Noviyatul; Fawaid, Moh. (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to analyze the role of leadership style and motivation in improving employee performance, using a systematic literature review method. Data collection was conducted through literature analysis, which was then processed using bibliometric techniques with the help of VOSviewer 1.6.20 software. The study found that an appropriate leadership style, such as transformational or participative leadership, can create a supportive work environment where employees feel valued and motivated to contribute their best. Additionally, motivation, both intrinsic and extrinsic, plays a crucial role in driving employees to achieve higher performance. The main conclusion of this study is that the synergy between effective leadership and proper motivation programs can enhance employees' capabilities, productivity, and job satisfaction. Consistent implementation of these two aspects allows organizations or companies to become more adaptive and competitive amid the dynamic changes in the business environment. The study's implications emphasize the importance of developing leadership programs that focus on increasing employee motivation as a strategy to achieve optimal and sustainable organizational performance.